Saúde do trabalhador e riscos de resíduo no ambiente hospitalar segundo a Norma Regulamentadora 32 - Cremer, Edivaldo; Vitta, Alberto de; Simeão, Sandra Fiorelli de Almeida Penteado; Conti, Marta Helena Souza de; Galdino, Maria José Quina; Borgato, Maria Helena [UNESP]; Marta, Sara Nader; Gatti, Marcia Aparecida Nuevo (My University, 2013)
Introduction: conditions of environment, health and safety at work has become essential for the quality of human life and the right of citizenship, representing a major challenge for governments and organizations. For the promotion of health at work, the anticipation of occupational hazards to prevent accidents has become indispensable. Objective: the study aimed to survey the occupational risk factors to which workers are exposed in the hospital setting, in a philanthropic hospital in the state of Paraná. Methodology: data were obtained through “checklist” based on protective measures against the risk of waste of Norm 32 laying down guidelines on safety and health of workers in health services. Results: results showed that the measures of protection against risks not covered waste was 33.3 %. Regarding subitems there was 16.7% of inadequacy in the packaging, 36.5 % in segregation, 60 % in temporary storage and 6.3 % in transport and offsite storage. Separately, the sharps were the most worrying subsection , with 86.11 % of inadequacy, represented by the practice of recapping , manual disconnection of needles, lack of safety device for disposal, in gallons of reused packaging products, limit exceeded filling and transportation along with other waste, packaging improperly, identification and signage absent in all these steps, becoming at risk of residue. Conclusion: we found that several units had risks of waste, allowing recommend proposals for interventions in health services to minimize the risks, or simply transform the practices established by law.

Introdução: as condições de ambiente, saúde e segurança no trabalho se tornaram essenciais para a qualidade de vida dos homens e o direito de cidadania, representando um grande desafio para os governos e organizações. Para a promoção da saúde no trabalho, a antecipação de riscos ocupacionais para prevenção de acidentes tornou-se indispensável. Objetivo: o presente estudo objetivou o levantamento dos fatores de risco ocupacionais a que estão expostos os trabalhadores do ambiente hospitalar, realizado em um hospital filantrópico do interior do Paraná. Metodologia: os dados foram obtidos por meio de “checklist” baseado nas medidas de proteção contra riscos de resíduos da Norma Regulamentadora 32, que estabelece as diretrizes sobre segurança e saúde dos trabalhadores dos serviços de saúde. Resultados: os resultados apontaram que as medidas de proteção contra riscos de resíduos não contempladas foram de 33,3%. Com relação aos subitens verificou-se 16,7% de inadequação no acondicionamento, 36,5% na segregação, 60% no armazenamento temporário e 6,3% no transporte e armazenamento externo. Isoladamente, os perfurocortantes foram o subitem mais preocupante, com 86,11% de inadequação, representados pelas práticas de reencape, desconexão manual de agulhas, ausência do dispositivo de segurança para descarte, acondicionamento em galões de produtos reutilizados, o limite de enchimento excedido e transporte juntamente com outros resíduos, acondicionamento de maneira inadequada, identificação e sinalização ausentes em todas essas etapas, constituindo-se em risco de resíduo. Conclusão: constatou-se que diversas unidades apresentaram riscos de resíduos, permitindo recomendar propostas de intervenções nos serviços de saúde para minimização dos riscos existentes, ou simplesmente transformação das práticas estabelecidas pela legislação vigente.
Occupational health and environmental risks of waste in hospital after the regulatory standard 32
Keywords: Worker’s health; Occupational hazards; Health waste; Regulatory Standard 32; Saúde do trabalhador; Riscos ocupacionais; Resíduos de saúde; Norma Regulamentadora 32